Comparative Analysis of Airborne Particle Concentrations in Textile Industry Environments Throughout the Workday - Emilia Visileanu; Korinna Altmann; Raluca Stepa; Maria Haiducu; Paul Tiberiu Miclea; Alina Vladu; Felicia Dondea; Marian Catalin Grosu; Razvan Scarlat (Microplastics, 2025)
This paper addresses the growing concern surrounding microplastic pollution, particularly within the textile industry, and the associated potential health risks linked to the inhalation and ingestion of microplastic particles. Microplastics, defined as plastic particles smaller than five millimeters, are increasingly found not only in aquatic environments, but also in soils, air, and food. Although research on the health impacts of microplastics is still emerging, early studies indicate that these particles could contribute to health issues, including oxidative stress, inflammation, and cardiovascular diseases. Notably, individuals with higher concentrations of plastics in arterial plaques are more susceptible to heart attacks and strokes. In the textile industry, synthetic fibers such as polyester, nylon, and acrylic release microplastics into the air during production. The paper discusses a study conducted in a textile company that processes polyester yarns, where airborne microplastic concentrations were measured at various locations throughout the day. Particle sizes ranging from 0.3 nm to 10 nm were analyzed, revealing the presence of polyester polymers in the particulate matter. These findings underscore the widespread nature of microplastic pollution, particularly in industrial settings, and raise concerns about the health risks associated with prolonged exposure to airborne microplastics. While further research is necessary to fully understand the extent of these health impacts, preliminary data suggest a troubling link between microplastic inhalation and cardiovascular conditions.